Technologies used for heavy metals removal from wastewater - Harun, Hasnida; A. Hamid, Hazren; Mohamed Sunar, Norshuhaila; Ahmad, Faridahanim; Ali, R.; Hamidon, Nuramidah; Baul, Mary Lyana (Penerbit Uthm, 2018)
Heavy metals are the elements found in periodic table that exhibits metallic properties and characterised by 5 g/cm3 of density [1]. Heavy metals are contaminants from inorganic source that tend to pollute the ecosystem due to anthropogenic activities like mining, welding, semiconductors and electrical appliances manufacturing industries. Heavy metals can be broken down or metabolised. The presence of heavy metals without any proper management can bring negative effects to human and ecosystem.